Optimization of the process of primary school age children adaptation: practical expertise - Vitalii Kashuba; Nataliia Goncharova (Kazimierz Wielki University, 2018)
Introduction of innovative technologies to the system of primary education has made it possible to consider new mechanisms for the implementation of health-forming activities in the process of physical education, which greatly expands the arsenal of tools and methodological approaches to organize a process of physical education. Existing scientific progress in the issues of forming the health of primary school age children does not fully provide insight into the mechanisms of this type of activity and is limited in the complex influence on the process of children adaptation to school studying conditions. The objective of the study is to assess the effectiveness of practical expertise in optimizing the processes of primary school age children adaptation to the conditions of study. Methods of research are theoretical analysis of data from scientific, methodical and specialized literature, pedagogical experiment, assessment of the primary school age children adaptation to the conditions of study by T. I. Lyasota comprehensive method, mathematical statistics. Research results. The process of adaptation to school conditions of primary school children is analyzed. The author's concept of health-forming technologies in the process of physical education of primary school age children is introduced, it is based on the use of active tourism means, the control function in the process of the concept implementation is defined. The directions of practical implementation of the author's concept are reviewed. The effectiveness of the proposed concept determined in the process of forming a pedagogical experiment was analyzed. 51 students of the first grade (23 boys and 28 girls) participated in the study, they were divided into control and experimental groups. The practical implementation of the concept of health-forming technologies in the process of physical education of primary school age children contributed to improving the processes of primary school age children adaptation to the conditions of school studying at EG students compared with CG students.